CORFEBOL AND HIS/HER CARÁTER SOCIALIZADOR BETWEEN BOYS AND GIRLS IN THE CLASSES OF PHYSICAL EDUCATION. (Fiep Bulletin - online, 2014)
What unchained the present study went to the observation of the boys' conduct in relation to participation of them, in the same team, when of the accomplishment of the games pré-sport or sport, such as: handball, volleyball etc. Those two groups along the years in that the Physical education has been taught at the Brazilian schools, they demonstrate a total social separation, when the subject is the collective games.  The boys when questioned of the reason of that behavior, they justify his/her discrimination for the fact, that the girls, don't possess enough ability so that their teams can arrive the victory. That type of behavior begins, precocemente, to develop an attitude highly discriminadora and a factor of quite preoccupying social exclusion, because, for a society it can become a great nation is necessary that there is a great cooperation between men and women.    After probing those two groups informally, on the reason of such procedure, I noticed that the cause was related with basic needs of self-esteem and of other aspects comportamentais and social.  The central subject of that study is ruled in the prevalence of the presence of some students that have a conduct comportamental dominant ego in the questioned groups. And in the harmful character that such behavior can present in his/her future lives, concerning the social conviviality and the social interaction. The concern, because, with the theme corfebol and his/her character socializador as intervening factor, for the increase of the goal task and the decrease of the goal ego in the boys' behavior in relation to the girls' participation in the sport games in the classes of Physical education appears exactly of the understanding that every individual should be motivated with a "green sign" that it continues or stop with a certain behavior, in all of the social spaces, above all in the educational spaces.  Being permitted that all can maintain or to modify his/her motive conduct in the proposed activities and enjoy their benefits, being valued the individual capacities and the several stages of the child's development psicomotor, not looking for the athletes' formation, but the human being's global formation.
Keywords: Corfebol; socialization; goal-ego; put task